Max Weber - made in the USA? (Sociologisk Forskning, 2000)
Max Weber - Made in the USA?Max Weber took deep impression from his American journey in 1904, which is manifested in several of his texts, not only The Protestant Ethnic and the Spirit of Capitalism, but also the so called twin lectures. He also influenced many American scholars, many of them originally European migrants. Weber’s American contacts are relevant for several themes, such as the reciprocity over the Atlantic ocean and the proper pursuit of intellectual history. America was more receptive to Weber’s methodology, while his views on politcs have not entered the parnassus to the same extent. Weber’s Scandinavian contacts are sparse, except for an “apocryphal” visit documented by John Landquist.